Implementasi Prinsip Syura dalam Sistem Pemerintahan Daerah - Putry Kartika Aprilya; Agus Tohawi (Universitas Pangeran Diponegoro Nganjuk, 2024)
The principle of syura is a fundamental Islamic concept emphasizing the importance of consultation in decision-making processes. In the context of regional governance, implementing the principle of syura can foster inclusive, fair, and beneficial policies for communities. This article explores the application of syura in local governments, including its role in legislation, public policy management, and community empowerment. Using normative and empirical analysis, this study finds that integrating syura values into modern governance systems is relevant for enhancing transparency, accountability, and strengthening public participation. Thus, syura is not only a theoretical value but also a practical solution to address the challenges of better regional governance.